(untitled) (Journal of Applied Oral Science, 2021)
The study of dental development in individuals born with cleft lip and palate (CLP) serves to determine when orthodontic intervention should start. Objective: To evaluate the permanent second molar development in children born with cleft lip and palate according to Demirjian’s and Nolla’s methods. Methodology: Out of a total of 513 digital panoramic radiographs, 113 pairs of children aged 3 to 16 years were selected. The exams were from children born with or without cleft lip and palate, of the same sex, with an age difference of up to 30 days. The images were analyzed by three examiners and reliability was checked through intra-examiner agreement by the Kappa test. The data were analyzed by Wilcoxon's and Mann-Whitney tests according to each dataset. Results: The findings indicated delayed development of the permanent second molars in children with CLP (P<0.001). The development of the right permanent second molar was delayed compared to the left molar in children with CLP. Moreover, mandibular teeth showed significantly earlier development than maxillary teeth in both the case and control groups. There was no significant difference in the development of permanent second molars between sexes. Conclusion: Children with CLP presented delay in the development of permanent second molars.